Inflation and Fiscal Deficits : The Irrelevance of Debt and Money Financing - Barrionuevo, Jose. (Washington, D.C. : International Monetary Fund, 1992)
The purpose of this paper is to present a model that circumvents the requirement of explicitly setting a period in which the fiscal budget is to be balanced, yet implies that increases in the growth of public debt are bound to increase inflation when there is no perceived commitment to reduce the fiscal deficit. The model is based on a modified version of the cash in advance constraint. The results of numerical simulations suggest that an increase in the growth of debt to finance current consumption leads to an equal increase in inflation. The timing of this increase varies with the size of the deficit and the pace of economic growth. It is shown that small increases in small deficits yield fairly significant increases in inflation. Three policy conclusions are offered.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet